Sustainable livelihood approach with gender-social inclusion perspective for child labor prevention and remediation in rural areas of South Sulawesi, Indonesia - Idrus, Idham Irwansyah; Tamrin, Sopian; Amandaria, Riri; Wahda, Muhammad Aksha; Fitriana (Frontiers in Sociology, 2025)
Child labor is a global issue commonly found in low- and middle-income countries. A prevention and remediation system based on community knowledge through the Sustainable Livelihood Approach (SLA) with Gender Social Inclusion (GESI) is needed. This study was conducted in three regions with different topographical and geographical characteristics, using qualitative methods and the Participatory Rural Appraisal (PRA) technique, including interviews, focus group discussions, participatory mapping, transects, and seasonal calendars. Findings indicate that child labor is driven by poverty, household characteristics, parents’ education and employment, and limited access to educational services and labor markets. Social, natural, financial, and human capitals serve as strategies for prevention and management of child labor. Utilizing these capitals can be implemented in child labor monitoring and remediation, which can also be conducted as voluntary social audits by community groups. The main recommendation is to establish or assign groups responsible for ensuring the continuity of child labor prevention and intervention efforts.